Single-crystalline CdTe nanowire field effect transistors as nanowire-based photodetector - Shaygan, Mehrdad; Davami, Keivan; Kheirabi, Nazli; Baek, Changi Ki; Cuniberti, Gianaurelio (Giovanni); Meyyappand, M.; Lee, Jeong-Soo (Physical Chemistry Chemical Physics, 2014)
The electronic and photoconductive characteristics of CdTe nanowire-based field effect transistors were studied systematically. The electrical characterization of a single CdTe nanowire FET verifies p-type behavior. The CdTe NW FETs respond to visible-near infrared (400-800 nm) incident light with a fast, reversible and stable response characterized by a high responsivity (81 A W-1), photoconductive gain (∼2.5 × 104%) and reasonable response and decay times (0.7 s and 1 s, respectively). These results substantiate the potential of CdTe nanowire-based photodetectors in optoelectronic applications. © the Partner Organisations 2014.
CRIS-Team Scopus Importer:2023-03-20